Pelatihan Pembuatan Media Presentasi PowerPoint bagi Siswa Kelas IX MTs Muslimat NU Palangka Raya sebagai Bekal Kesiapan Menuju SMA/MA - Hikmah, Aida Nurul; Abdullah, Abdullah; Rahimah, Rahimah (Al-DYAS, 2025)
This community service initiative was driven by the importance of strengthening students' digital skills and creativity in response to the demands of technology-based learning. The objective was to enhance the digital competencies and creativity of ninth-grade students at MTs Muslimat NU Palangka Raya through a training program on creating presentation media using Microsoft PowerPoint. The method employed was Participatory Action Research (PAR), involving students actively throughout all stages of the activity, from planning and implementation to evaluation. The training was conducted in four main phases: introduction to slide identity, typing and text formatting, inserting images or photos, and creating slide transitions and animations. Evaluation results showed a significant improvement in students’ understanding and skills in operating PowerPoint, particularly in visual design, use of animation features, and constructing communicative slides. Beyond technical skills, the training also fostered affective development, including increased self-confidence, creative thinking abilities, and collaborative skills. The conclusion of this activity affirms that the training successfully equipped students with fundamental capabilities to develop digital presentation media relevant to higher levels of education, while also supporting the advancement of technology literacy at the madrasah level.